2014
DOI: 10.1002/hipo.22293
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of early life stress on hippocampus and amygdala volume as a function of emotional abilities

Abstract: Early life stress (ELS) is known to have considerable influence on brain development and affective functioning. Previous studies in clinical populations have shown that hippocampus and amygdala, two central structures of limbic emotion processing circuits, are predominantly affected by early stress exposure. Given the inconsistent findings on ELS-related effects in healthy populations and the associations of ELS and affective functioning, the question arises which additional emotion-relevant variables need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…However, hippocampal volume seems to be unaffected in children but not in adults with maltreatment-related PTSD, suggesting an initially volumetrically normal hippocampus with subsequent abnormal disrupted development (443). With respect to amygdala, the results from human studies regarding the volumetric effect of ELS/CT are inconclusive, with some studies reporting reduced volume (416,428,430,444), some differential effects according to specific type of ELS/CT (432,445), and some even greater amygdala volume (in non-human primates) (446). However, findings are conclusive concerning amygdala responsiveness, as ELS/CT has been repeatedly associated with facial threat-or negative-emotion-related amygdala hyper-responsiveness (416,417,447,448).…”
Section: Structural and Functional Imaging Findingsmentioning
confidence: 99%
“…However, hippocampal volume seems to be unaffected in children but not in adults with maltreatment-related PTSD, suggesting an initially volumetrically normal hippocampus with subsequent abnormal disrupted development (443). With respect to amygdala, the results from human studies regarding the volumetric effect of ELS/CT are inconclusive, with some studies reporting reduced volume (416,428,430,444), some differential effects according to specific type of ELS/CT (432,445), and some even greater amygdala volume (in non-human primates) (446). However, findings are conclusive concerning amygdala responsiveness, as ELS/CT has been repeatedly associated with facial threat-or negative-emotion-related amygdala hyper-responsiveness (416,417,447,448).…”
Section: Structural and Functional Imaging Findingsmentioning
confidence: 99%
“…Our secondary aim was to extend research on the interaction of childhood and recent stress to individuals in the early stages of mental disorder. For example, childhood maltreatment has been linked to both increased and decreased amygdala volumes in adults [Aas et al, 2012, Cisler et al, 2013, Dean et al, 2014, Frodl et al, 2010, Pechtel et al, 2013, Aust et al, 2014, Hoy et al, 2012, Veer et al, 2015. The advantages of using this trans diagnostic approach in research, in contrast to categorical diagnostic grouping, are discussed at length elsewhere [Casey et al, 2013, Cuthbert, 2014, Cuthbert and Insel, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, we wished to ascertain whether variability in childhood trauma neuroimaging research stems from differences in recent stress. For example, childhood maltreatment has been linked to both increased and decreased amygdala volumes in adults [Aas et al, 2012, Cisler et al, 2013, Dean et al, 2014, Frodl et al, 2010, Pechtel et al, 2013, Aust et al, 2014, Hoy et al, 2012, Veer et al, 2015. To do so, we designed a study in line with the proposal of Nederhof and Schmidt [2012].…”
Section: Introductionmentioning
confidence: 99%
“…7 In contrast, studies investigating healthy individuals with lower alexithymia scores have found no association or a positive association between alexithymia and grey matter volume. [30][31][32][33] Our aim was to find brain structural correlates of alexithymia in lifetime MDD and brain structural correlates that were differentially associated with alexithymia in healthy controls and patients with MDD. According to the literature, 30,32 people with low alexithymia scores exhibit a positive association between alexithymia and grey matter volume.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Our aim was to find brain structural correlates of alexithymia in lifetime MDD and brain structural correlates that were differentially associated with alexithymia in healthy controls and patients with MDD. According to the literature, 30,32 people with low alexithymia scores exhibit a positive association between alexithymia and grey matter volume. Thus, we hypothesized a positive association between alexithymia and grey matter volume in FFG and ACC in the healthy controls.…”
Section: Introductionmentioning
confidence: 99%